Realization Of Real-Time Hardware-In-The-Loop For A Liquid Level With Open-Loop Ziegler Nichols Technique - Kamarudin, Muhammad Nizam; Md. Rozali, Sahazati; Hairi, Mohd Hendra; Hanaffi, Farhan; Mohd Aras, Mohd Shahrieel; Mohd Zambri, Mohd Khairi (Penerbit Universiti, UTeM, 2018)
This paper presents the realization of a real-time hardware-in-the-loop (HIL) for a liquid level control system. Multifarious controllers that were proposed in the previous literature are constrained within simulation platform. Several advanced control configurations are implemented in the hard-wire platform that incurs complex programming and requires computational burden. These kind of control configurations do not permit the operator to tune the control parameter online. Moreover, the parameters inside the microcontroller are unobservable to the operators. As such, the need to implement a real-time HIL for a liquid level control system worthwhile to the operators. It gives intuitive configuration and user-friendly application to the operators because the tuning process can be implemented in didactic manner. Furthermore, the controller design phase can be conducted with lees programming burden. Implementing the HIL requires three phases. The tank must be calibrated to obtain a linear relationship between the voltage and the water level. Afterward, the open-loop Ziegler Nichols is exploited to tune the parameters of three term Proportional-Integral-Derivative controller. The controller is then implemented in the MATLAB SIMULINK platform in the host computer. The result shows that the proposed real-time configuration guarantees the asymptotic tracking of the demanded water level with only 1.247% steady state error.